2021
DOI: 10.1126/sciadv.abe4577
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D deficiency exacerbates UV/endorphin and opioid addiction

Abstract: The current opioid epidemic warrants a better understanding of genetic and environmental factors that contribute to opioid addiction. Here we report an increased prevalence of vitamin D (VitD) deficiency in patients diagnosed with opioid use disorder and an inverse and dose-dependent association of VitD levels with self-reported opioid use. We used multiple pharmacologic approaches and genetic mouse models and found that deficiencies in VitD signaling amplify exogenous opioid responses that are normalized upon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 45 publications
0
20
1
Order By: Relevance
“…Vitamin D 3 also targets opioid receptor signaling, as vitamin D 3 supplementation modulates expression of genes involved in the signaling pathway and reduces neuropathic pain (193). Vitamin D 3 deficiency is recently reported to increase risk for opioid dependence, possibly due to deficiencies in VDR signaling (115), suggesting interactions between VDR with other receptors that regulate nervous system function. Furthermore, vitamin D 3 is recently reported as an agonist of the calcium-selective channel TRPV1 which mediates pain sensation (142).…”
Section: Vitamin Dmentioning
confidence: 99%
“…Vitamin D 3 also targets opioid receptor signaling, as vitamin D 3 supplementation modulates expression of genes involved in the signaling pathway and reduces neuropathic pain (193). Vitamin D 3 deficiency is recently reported to increase risk for opioid dependence, possibly due to deficiencies in VDR signaling (115), suggesting interactions between VDR with other receptors that regulate nervous system function. Furthermore, vitamin D 3 is recently reported as an agonist of the calcium-selective channel TRPV1 which mediates pain sensation (142).…”
Section: Vitamin Dmentioning
confidence: 99%
“…Other promising candidate RXRα binding partners include 1) RXRγ, which is known to contribute to striatal- and dopamine-dependent locomotion 18 and depressive-like 1921 behaviors, 2) NURR77/NR4A1, an IEG and orphan receptor associated with cocaine 52 and stress 53 behaviors that we here found positively correlated with RXRα expression (Fig. 2e), 3) RARs and PPARs because the enzymes that deliver retinoic acid to RAR/RXR or PPAR/RXR complexes – CRABP2 and FABP5 respectively – differentially contribute to addiction- 15, 16 and depression-related 17 behaviors, and 4) VDRs, as vitamin D deficiency was recently linked with opioid addiction 54 . Ultimately, a finer dissection of RXRα binding partners could better explain some of the cell-type-, region-, drug- and drug-regimen-specificity of drug-induced transcriptional programs, as these likely result not from the recruitment of one given transcription factor but rather of several factors that could be partly harmonized by RXRα, among others.…”
Section: Discussionmentioning
confidence: 65%
“…A study found that patients with a vitamin D deficiency were more likely to develop postoperative OUD and required a higher total opioid dose of an additional 98.7 morphine milligram equivalent dose, indicating that vitamin D may be a predictor for the onset of OUD ( 27 ). A recent study investigated retrospectively two separate populations, and found that vitamin D deficient or insufficient individuals are more likely to use opioids ( 28 ).…”
Section: Resultsmentioning
confidence: 99%